Satellite remote sensing and the integration of 6G communication and remote sensing - Wenjia XU; Yixu WANG; Mugen PENG (Dianxin kexue)
Satellite remote sensing is an important means for humans to achieve high-resolution earth observation, and it has gradually become an important component supporting economic and social development as well as national defense and security.6G pursues deep integration of communication, perception, and computation, and communication and remote sensing integration has become an important feature of it.The development of satellite remote sensing at home and abroad were reviewed, the existing system architecture of satellite remote sensing systems and the integrated system architecture of communication and remote sensing in the 6G era were outlined, and the typical satellite remote sensing technologies and the latest research progress driven by artificial intelligence were elaborated on.In response to the trend of integrating satellite communication and remote sensing in the 6G era, the technical challenges and development trends of realizing the combination of “one satellite, multiple uses, multi-satellite networking, multi-network integration, and intelligent services” were discussed.